Theoretical and experimental studies of the Coriolis mass flowmeter - Sultan, G. (Cranfield University, 1990)
The Coriolis sass flowaeter is modelled using the theory of vibrating beams. Tube deformations for the fundamental mode and the next two nodes of natural (out-of-plane) vibration are worked out for many tube geometries. An improved model taking into account the effects of elastic boundary conditions and added masses of the electromagnetic drive and detectors is also discussed. A method for predicting the optimum detection positions is suggested in relation to signal-to-noise ratio. In addition, an argument for prediction of the effects of a dilute suspension of small bubbles or particles in the fluid is presented. Finally, experimental studies are conducted in order to demonstrate the validity of the theoretical models.